2009
DOI: 10.5194/angeo-27-1363-2009
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous variations of <I>Nm</I>F2 over the Argentine Islands: a statistical study

Abstract: Abstract. We present a statistical study of variations in the F2-layer peak electron density, NmF2, and altitude, hmF2, over the Argentine Islands ionosonde. The critical frequencies, foF2, and, foE, of the F2 and E-layers, and the propagation factor, M(3000)F2, measured by the ionosonde during the 1957-1959 and 1962-1995 time periods were used in the statistical analysis to determine the values of NmF2 and hmF2. The probabilities to observe maximum and minimum values of NmF2 and hmF2 in a diurnal variation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Lee et al [2011] recently described these ably in their introduction, so only a few papers will be mentioned here. A number of studies extended Berkner et al's [1936] original work [e.g., Yonezawa, 1971;Torr and Torr, 1973;Rishbeth and MullerWodarg, 2006;Pavlov and Pavlova, 2009]. The Torr and Torr [1973] study described the difference in the winter anomaly at solar maximum and minimum.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lee et al [2011] recently described these ably in their introduction, so only a few papers will be mentioned here. A number of studies extended Berkner et al's [1936] original work [e.g., Yonezawa, 1971;Torr and Torr, 1973;Rishbeth and MullerWodarg, 2006;Pavlov and Pavlova, 2009]. The Torr and Torr [1973] study described the difference in the winter anomaly at solar maximum and minimum.…”
Section: Introductionmentioning
confidence: 97%
“…Their work, however, used a definition of the winter anomaly that effectively included the annual anomaly as well and did not attempt to describe how the winter anomaly developed over a solar cycle. Pavlov and Pavlova [2009] suggested that the Torr and Torr [1973] study might not make an accurate calculation of the intensity of the winter anomaly because of contamination by magnetically disturbed conditions. However, as geomagnetic storms are relatively rare events (as defined by Kp > 5), their contribution to the averages used by Torr and Torr was probably relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…There is an anomaly in f 0 F 2 behaviour at UAS in summer when the critical frequency in nighttime is higher than in daytime [13]. This explains why the probability of IAR registration at UAS in summer is much lower than at the other stations.…”
Section: Such a Phenomenon Is Named Ionospheric Alfvén Resonator (Iarmentioning
confidence: 83%
“…Close to the midnight sector, the F 2 -layer is raised and maintained by plasma drift. As the ionosphere is sunlit during the long summer day in January N m F 2 increases producing the observed higher N m F 2 values close to midnight (Pavlov et al, 2008;Pavlov and Pavlova, 2009). …”
Section: Behaviour Of F O Fmentioning
confidence: 99%
“…This behaviour indicates that diurnal variations of f o F 2 have a weak solar zenith dependence. These diurnal variations of f o F 2 are explained by Pavlov and Pavlova (2009) by changes in the neutral wind-induced drift along the magnetic field lines and by neutral density variations. A poleward neutral wind causes a lowering of the F 2 -region height and a reduction of the density peak N m F 2 due to an increase in the loss rate of O + ions with N 2 and O 2 .…”
Section: Behaviour Of F O Fmentioning
confidence: 99%